AIM2 Mediates Inflammation-Associated Renal Damage in Hepatitis B Virus-Associated Glomerulonephritis by Regulating Caspase-1, IL-1β, and IL-18. (20th February 2014) - Zhen, Junhui; Zhang, Le; Pan, Jiachao; Ma, Shumin; Yu, Xiaojian; Li, Xiaobo; Chen, Shijun; Du, Wenjun
Abstract : Background & Aims . AIM2 plays an important role in innate immunity, but its role in regulating the immune response to hepatitis B virus (HBV) is unknown. We hypothesized that AIM2 expression is positively correlated with HBV-mediated inflammation in patients with HBV-associated glomerulonephritis (HBV-GN), potentiating inflammation and leading to renal damage. We therefore analyzed the expression of AIM2 and inflammatory factors in HBV-GN tissues and cell lines relative to the inflammatory response to HBV infection and HBV status. Methods . Seventy-nine patients with chronic nephritis (CN) were included: 54 with HBV-GN and 24 with chronic glomerulonephritis (CGN). Expression of AIM2, caspase-1, and IL-1 β was detected by immunohistochemistry in renal biopsies from each patient. Following siRNA-mediated knockdown of AIM2 in HBV-infected and HBV-uninfected human glomerular mesangial (HGM) cells, expression of caspase-1, IL-1 β, and IL-18 was detected by qRT-PCR and Western blot. Results . AIM2 expression in HBV-GN biopsies (81.4%) was significantly higher than in CGN (4.0%) and positively correlated with caspase-1 and IL-1 β expression in HBV-GN. In vitro, AIM2 knockdown reduced caspase-1, IL-1 β, and IL-18 expression in HBV-infected and HBV-uninfected HGM cells. Conclusion . AIM2 elevation during HBV infection or replication may contribute to inflammatory damage, thus providing a putative therapeutic target for HBV-GN.